2021
DOI: 10.1037/aap0000213
|View full text |Cite
|
Sign up to set email alerts
|

Family and friend responses to Filipino loved ones experiencing partner abuse.

Abstract: Community-based research shows that 22% of Filipino Americans report experiencing at least one form of partner abuse (PA) during their lifetime, a higher prevalence rate than those documented among other Asian ethnic groups (Asian Pacific Institute on Gender-Based Violence, 2018). Victims with support resources are less likely to experience negative health outcomes and revictimization, and one of the most important sources of support is family and friends (Coker, Watkins, Smith, & Brandt, 2003). The vast major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 71 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…We found that family and friends used numerous communication and action responses to stay connected to their loved ones and support their loved ones’ safety and welfare (see Table 1). Family members and friends communicated with loved ones by affirming their feelings and experiences; sharing information about PA or sharing their own PA experiences; challenging loved ones’ perceptions of their relationship and behaviors; remaining nonjudgmental; and avoiding discussions about the PA or hiding the PA. Filipino family and friends also took actions to respond, including connecting interpersonally with survivors and their families; setting boundaries; intervening directly during abusive or threatening situations; consulting with other social network members; monitoring their loved ones’ safety/welfare; and providing resources (Chronister et al, 2020). Chronister et al (2020) provided a first glimpse at the responses of Filipino network members’ responses to loved ones experiencing PA, but did not detail what contextual and cultural factors influenced network members’ response decisions, and how…”
Section: Pa In Filipino Communitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that family and friends used numerous communication and action responses to stay connected to their loved ones and support their loved ones’ safety and welfare (see Table 1). Family members and friends communicated with loved ones by affirming their feelings and experiences; sharing information about PA or sharing their own PA experiences; challenging loved ones’ perceptions of their relationship and behaviors; remaining nonjudgmental; and avoiding discussions about the PA or hiding the PA. Filipino family and friends also took actions to respond, including connecting interpersonally with survivors and their families; setting boundaries; intervening directly during abusive or threatening situations; consulting with other social network members; monitoring their loved ones’ safety/welfare; and providing resources (Chronister et al, 2020). Chronister et al (2020) provided a first glimpse at the responses of Filipino network members’ responses to loved ones experiencing PA, but did not detail what contextual and cultural factors influenced network members’ response decisions, and how…”
Section: Pa In Filipino Communitiesmentioning
confidence: 99%
“…The aim of the present study, therefore, was to build on findings from a previous study (Chronister et al, 2020) to identify the contextual and cultural factors that influenced family members’ and friends’ responses to PA, and how these factors influenced their response choices. Table 1 provides a results summary of network members’ response choices from our previous study (Chronister et al, 2020).…”
Section: Pa In Filipino Communitiesmentioning
confidence: 99%
See 3 more Smart Citations